An Alternative Adhesive Strategy to Optimize Bonding to Root Dentin - DALKILIÇ, EVRİM; Belli, Sema; Cobankara, Funda Kont; Ozcopur, Betul; Eliguzeloglu, EVRİM; Eskitascioglu, Gurcan (My University, 2011)
Introduction: This study examined the hypothesis that the shear-bond strengths of AH Plus (AH) and Hybrid Root Seal (HRS) to root dentin might be optimized by using a powdered dentin-reinforced bonding procedure. Methods: The surfaces of root halves obtained from extracted human premolars were ground (800-grit silicon carbide paper), treated (5.25% NaOCl 17% EDTA for 5 minutes followed by distilled water) and randomly allocated into two groups according to the sealer and then into three subgroups according to bonding procedure. Dentin particles with a maximum size of 25 mu m were incorporated into the adhesive of Clearfil Liner Bond 2V, and groups were created as follows: no adhesive, adhesive alone, and with powdered dentin reinforced adhesive; 3 x 3 mm high buildups were created using sealer and allowed to set (37 degrees C, 100% humidity, 72 hours). Shear tests were performed (1 mm/min). Data were calculated as MPa and analyzed (two-way analysis of variance, Tukey test). Results: A significant difference was found between the groups (P = .000). Adhesive or reinforced adhesive had a negative effect on the shear-bond strength of AH, but they significantly increased the shear-bond strength of HRS (P = .000). HRS showed a similar bond strength with either adhesive alone or adhesive reinforced with powdered dentin. AH group was characterized by mixed failure, whereas the predominant failure type of the HRS group was cohesive failure within the sealer. Conclusions: Reinforcing adhesive resin with powdered dentin may be considered an alternative for optimizing the bonding of methacrylate-based sealers to root dentin and might affect the shear bond strength. (J Endod 2011;37:1427-1432)